Evaluation of the In Vitro Detection of the Hypercoagulable State Using the Thrombin Generation Test and Plasma Clot Impedance Test - Peck, Sanford D (Thrombosis and Haemostasis, 1979)
This study reports the correlation of the thrombin generation test and the plasma clot impedance test with clinical evidence of hypercoagulability. Thrombin generation is increased and the rate of change of plasma from a liquid to a gel (clot impedance) is increased in situations where the risk of thrombosis is increased.These situations include increasing clinical signs and/or symptoms of thromboembolism, positive lung scans, postoperative total hip replacement, patients over 40 years old, low serum antithrombin III, thrombocytosis, transient cerebral ischemia, and positive isotope venogram for thrombosis. The two tests failed to indicate a significant effect of antiplatelet drugs on the hypercoagulable state.This study shows that the thrombin generation and plasma clot impedance tests are practical, rapid and useful tests for the detection and monitoring of the hypercoagulable state.